2015
DOI: 10.1002/ejoc.201500186
|View full text |Cite
|
Sign up to set email alerts
|

Phenyliodine Bis(trifluoroacetate) (PIFA) as an Excellent Promoter of 2‐Deoxy‐2‐phthalimido‐1‐thioglycosides in the Presence of Triflic Acid in Glycosylation Reactions

Abstract: A combination of phenyliodine bis(trifluoroacetate) (PIFA) and trifluoromethanesulfonic acid was found to be an effective activator for the glycosylation reaction, of which the glycosyl donor was p‐(octyloxy)phenyl 3,4,6‐tri‐O‐acetyl‐2‐deoxy‐2‐phthalimido‐1‐thio‐D‐glucopyranoside or p‐(octyloxy)phenyl 3,4,6‐tri‐O‐acetyl‐2‐deoxy‐2‐phthalimido‐1‐thio‐D‐galactopyranoside. The reaction proceeded with good yields when naturally occurring and derived alkanols, such as cholestanol, (–)‐menthol, 1‐ and 2‐adamantanols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…31,32) Thus, we have recently developed novel methods of hypervalent iodine-induced glycosylation of thioglycoside. 33) Besides our study, a few methods have been reported as for the activation of thioglycosides with hypervalent iodines to date [34][35][36] ; however, activation of disarmed thioglycosides with hypervalent iodines still remains impractical and unavailable in the synthesis of biologically active oligosaccharides. Herein, we now would like to report a new organosulfur participating promoter system in which both the armed and disarmed thioglycoside donors can be activated by using the hypervalent iodine reagent (Chart 1).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…31,32) Thus, we have recently developed novel methods of hypervalent iodine-induced glycosylation of thioglycoside. 33) Besides our study, a few methods have been reported as for the activation of thioglycosides with hypervalent iodines to date [34][35][36] ; however, activation of disarmed thioglycosides with hypervalent iodines still remains impractical and unavailable in the synthesis of biologically active oligosaccharides. Herein, we now would like to report a new organosulfur participating promoter system in which both the armed and disarmed thioglycoside donors can be activated by using the hypervalent iodine reagent (Chart 1).…”
mentioning
confidence: 83%
“…Based on our previous investigation of the glycosylation, 33) we examined the glycosylation reaction of methyl 2-deoxy-2-phthalimido-3,4,6-tri-O-acetyl-1-thio-D-glucopyranoside 1a with 1-O-methyl 2,3,4-tri-O-benzyl-α-D-glucopyranoside 2 using the combination of phenyliodine(III) bis(trifluoroacetate) (PIFA) with various acids. As a result, the reaction with PIFA and trifluoromethanesulfonic acid (TfOH) afforded the best yield (77%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, glycosides with a phthalimido group in the C‐2 position were found to be activated by the hypervalent iodine compound, phenyliodine bis(trifluoroacetate) (PIFA) in the presence of triflic acid . Proper optimization of the reaction conditions of this metal‐free glycosylation afforded the coupled product in significant yields.…”
Section: Glycosylationsmentioning
confidence: 99%
“…The Neu5Ac-a-2,3-lactosamine donor with a2 -phthalimido group insteado fa2-acetamido group favored the glycosylationr eactionw ith lipids or proteins. [8] Several methods to synthesize LacNPhth and LacNHAc derivatives have been reported (Entries 1-10 in Ta ble1). [7b, 9] These methods can be categorized into two types:o ne using acceptors where both the C3-OH andC 4-OH are unprotected( Entries 1-10 apart from 4a nd 7i nT able 1) and the other using acceptors where only the C4-OH is unprotected( Entries 4a nd 7i n Ta ble 1).…”
Section: Resultsmentioning
confidence: 99%